ALMA-LEGUS. II.: the influence of subgalactic environments on molecular cloud properties - Finn, Molly; Johnson, Kelsey E.; Indebetouw, Remy; Costa, Allison H.; Adamo, Angela; Aloisi, Alessandra; Bittle, Lauren; Calzetti, Daniela; Dale, Daniel A.; Dobbs, Clare L.; Meyer, Jennifer Donovan; Elmegreen, Bruce G.; et al. (The astrophysical journal, 2024)
We compare the molecular cloud properties in subgalactic regions of two galaxies, barred spiral NGC 1313, which is forming many massive clusters, and flocculent spiral NGC 7793, which is forming significantly fewer massive clusters despite having a similar star formation rate to NGC 1313. We find that there are larger variations in cloud properties between different regions within each galaxy than there are between the galaxies on a global scale, especially for NGC 1313. There are higher masses, line widths, pressures, and virial parameters in the arms of NGC 1313 and the center of NGC 7793 than in the interarm and outer regions of the galaxies. The massive cluster formation of NGC 1313 may be driven by its greater variation in environment, allowing more clouds with the necessary conditions to emerge, although no one parameter seems primarily responsible for the difference in star formation. Meanwhile NGC 7793 has clouds that are as massive and have as much kinetic energy as the clouds in the arms of NGC 1313, but have densities and pressures more similar to those in the interarm regions and so are less inclined to collapse and form stars. The cloud properties in NGC 1313 and NGC 7793 suggest that spiral arms, bars, interarm regions, and flocculent spirals each represent distinct environments with regard to molecular cloud populations. We see surprisingly little difference in surface density between the regions, suggesting that the differences in surface densities frequently seen between arm and interarm regions in lower-resolution studies are indicative of the sparsity of molecular clouds, rather than differences in their true surface density.